Fashion, Image, and Consumerism: fashion editorials as a communication strategy for brands (ModaPalavra e-periódico, 2020)
This article aimed to address the theme of fashion editorialsas acommunication strategy and consumption for brands.Brings a general overview on consumption and fashioncommunication, as well as an explanation of what areeditorials, how these are made and for what they serve. Thisarticle was based on the bibliographyof several authors inorder to clarify the area and the communicative potential ofeditorials for fashion brands.
Keywords: fashion editorial; image; communication; consumption